Chronic stress in mice: how gut bacteria influence gene activity in key brain neurons - Wenxia Jiang; Yifan Li; Jie Yang; Xunmin Tan; Ruimin Tian; Guojing Ma; Jing Wu; Jianping Zhang; Yu Huang; Ping Liu; Minghao Yuan; Xiaodong Song; et al. (Translational Psychiatry)
Abstract Major depressive disorder (MDD) is a serious mental disorder. Increasing evidence suggests that changes of gut microbiota are involved in pathogenesis of depression, yet the underlying mechanisms remains unknown. Here, chronic unpredictable mild stress (CUMS) mice model was constructed to mimic depression. We characterized the microbial composition and function of control, bedding exchange, and CUMS mice through 16S rRNA gene and metagenomic sequencing. Additionally, single-nucleus RNA sequencing (snRNA-seq) was used to compare the transcriptomic changes in the hypothalamus of these three groups. We found that replacing the bedding of CUMS mice with that of control mice could reverse the depressive-like behaviors. The microbial signatures of bedding exchange group trended towards the control group at the genus level. The abundance of g_norank_f_Muribaculaceae significantly increased in the bedding exchange group compared to CUMS group. Meanwhile, we found that the CUMS mice were characterized by cell-specific transcriptomic changes in hypothalamus. Notably, the transcriptomes of excitatory neurons in the hypothalamus were mainly affected, and these changes could be effectively reversed by bedding exchange treatment. The gene modules analysis revealed that the gut microbiota mainly modulated glyoxylate and dicarboxylate metabolism as well as arginine biosynthesis in hypothalamic excitatory neurons. Our findings provide new insights into the pathogenesis of depression.